The use of poetry in remediation - Donaldson-Selby, Claudia (School of Education, 2016)
This dissertation presents an evaluation of a new method of teaching reading by means of a handbook for teachers and a workbook for children who have not learnt reading after being taught by the traditional methods in the classroom. The method uses poetry, mainly in doggerel and limerick form, assembled into a sequential and meaningful reading/spelling programme which, together with reference to phonics workbooks and reading books, trains the beginner reader up to the level of reading literacy. Research on the literature available shows that poetry has not yet been used as a total remedial programme. The efficacy of the need for remediation is examined, and remediation methods analysed for what they should include. Other avenues of remediation are explored, such as the gross and fine motor and perceptual schools of thought, and the language and auditory orientation to remediation, into which the Poetry Method neatly fits. Psychological theories - such as the behaviourist operative reward systems and the ideas of phenomenologists such as Rogers - that total healing can come about through renewed motivation and growth in self-esteem, are shown to be included in the Poetry Method.